The Need to Analyze the Assortment and Improve the Quality of Cosmetic Products for Consumers in Hot Climates - Ahmedjanova F.A. (Mathematical Statistician and Engineering Applications, 2023)
The article presents research data on the structure of the assortment of cosmetic products and ways to improve it for consumers in a hot, dry climate.